Antiepileptic drug treatment of rolandic epilepsy and Panayiotopoulos syndrome: clinical practice survey and clinical trial feasibility. Issue 1 (8th September 2014) - Mellish, Louise C; Dunkley, Colin; Ferrie, Colin D; Pal, Deb K
Abstract : Background: The evidence base for management of childhood epilepsy is poor, especially for the most common specific syndromes such as rolandic epilepsy (RE) and Panayiotopoulos syndrome (PS). Considerable international variation in management and controversy about non-treatment indicate the need for high quality randomised controlled trials (RCT). The aim of this study is, therefore, to describe current UK practice and explore the feasibility of different RCT designs for RE and PS. Methods: We conducted an online survey of 590 UK paediatricians who treat epilepsy. Thirty-two questions covered annual caseload, investigation and management practice, factors influencing treatment, antiepileptic drug preferences and hypothetical trial design preferences. Results: 132 responded (22%): 81% were paediatricians and 95% at consultant seniority. We estimated, annually, 751 new RE cases and 233 PS cases. Electroencephalography (EEG) is requested at least half the time in approximately 70% of cases; MRI brain at least half the time in 40%–65% cases and neuropsychological evaluation in 7%–8%. Clinicians reported non-treatment in 40%: main reasons were low frequency of seizures and parent/child preferences. Carbamazepine is the preferred older, and levetiracetam the preferred newer, RCT arm. Approximately one-half considered active and placebo designs acceptable, choosing seizures as primary and cognitive/behavioural measures as secondary outcomes. Conclusions: Management among respondents is broadly in line with national guidance, although with possible overuse of brain imaging and underuse of EEG and neuropsychological assessments. A large proportion of patients in the UK remains untreated, and clinicians seem amenable to a range of RCT designs, with carbamazepine and levetiracetam the preferred active drugs.